The Effect of TGfU (Teaching Game for Understanding) on Futsal Games for Junior High School - Andi Gunawan; Firmansyah Dlis; Johansyah Lubis; Desy Tya Maya Ningrum; Yafi Velyan Mahyudi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to determine the effectiveness of the teaching game for understanding (TGfU) method in improving futsal game skills. The method used in this research is experimental. The technique in sampling is using purposive sampling with the category of students who have basic skills of futsal games. The participants involved totaled 25 students (20 boys and 5 girls) and were divided into 5 teams. Each team received the same treatment with the TGfU learning method. The instruments used in the study used observations and interviews. Observation includes decision-making, skill execution, Successful Game performance, player participation, and Enjoyment. Data collection used a 1-4 Likert scale with statements 1 (very poor), 2 (poor), 3 (good) and 4 (very good). The research findings show that during the intervention, participants can show their performance in a futsal game. The form of skills that students learn and master can also provide their enjoyment during learning. Therefore, TGfU can be a pedagogical approach to physical education learning in terms of technique, and students' enjoyment in the game, and useful for organized futsal teaching-learning activities